Transporte de nutrientes e bactérias por escoamento superficial devido a aplicação de água residuária da suinocultura no solo - Cosmann, Natássia Jersak (2010)
The swine activity is a characteristic of the south region of Brazil, and in the State of Parana it has been of outstanding economical and social importance. However, this activity presents low environmental quality due to the generation of great volumes of liquid residues with elevated pollutant power due to his physical, chemical and microbiological characteristics. The destination of the swine wastewater (SW) is an important factor for the survival and expansion of this activity. The application of the SW in the ground it is an alternative destination the residues, however, it is necessary that studies be carried out considering the rates which must be applied in each regional situation so that this practice does not damage the environment, especially affecting water resources and public health through the addition of pathogens in surface waters. Accordingly, the objective was to evaluate the potential for diffuse pollution of the provision of ARS in a loamy soil without a cover. In order to achieve this goal, we used five doses of SW (0, 25, 50, 75 and 100 m3.ha-1) and simulated rainfall of 60 mm.h-1 to promote runoff. Fractions disposed on the surface of the plots allocated in the Experimental Center of Agricultural Engineering (NEEA) of Western Paraná State University (UNIOESTE), Cascavel, PR, were collected in five volumes sold during the duration of simulated rain and evaluated the pH, electrical conductivity (EC), series of solids, total nitrogen (N), ammonia nitrogen (NH4 +), nitrate + nitrite (NH3 -+NH2 -), phosphate (P), copper (Cu+2), zinc (Zn+2), potassium (K+), calcium (Ca+2), magnesium (Mg+2), sodium (Na+) and micro-environmental indicator organisms (total coliforms (TC) faecal coliforms (EC) and enterococci (ENT)) according to the methods described by Standards Methods for the Examination of Water and Wastewater (APHA, 1998). Proceeded to analyze the data through regression analysis, in which the model potential was shown for all parameters. It was observed that concentrations of N, N-NH4 +, NO3 -+NO2 -, P, K+, Na+, Ca+2, Mg+2, TC, EC and ENT disposed in the fractions were dependent on the applied doses of ARS, and may influence quality of soil and surface water. There was also the possibility of applying a single model to predict the behavior of N and its forms as well as the biological parameters analyzed. Since the exponents of the potential equations was proposed a matrix of potential polluter diffuse (MPPD), which allows display and compares their potential polluters among all parameters. The MPPD indicated that the chemical outweighs the biological parameters in the following order: CT> EC> ENT> N-NH4+> K+> Mg+2> NO3-+NO2-> P> N.